Estudios geoquímicos de tierras raras e itrio en rocas de la Formación El Cortijo, sierras septentrionales de la provincia de Buenos Aires - Lajoinie, María Florencia (2017)
El Cortijo Formation (NO Tandil city) has contrasting mineralogical, structural and metamorphic features with those of the rest the Sierras Septentrionales de la Provincia de Buenos Aires basement. It comprises mylonitized low grade metamorphic rocks preliminarily classified, in former time, as metacherts, metabasalts and metawakes. Detailed analysis of rare earth elements (REE) in gray-whitish (GB) and gray-green-bluish (GVA) chert samples allowed a certain classification of these rocks. The obtained multielement diagram, normalized to Post-Archean Australian Shale (PAAS), shows a flat distribution in light rare earth element (LREE) and depleted contents ofheavy rare earth element (HREE) for GVA. The GB presents a different design, similar to that of a Greenstone Belt chert of 3.71-3.81 Ga, characterized by very positive anomalies in La (1.29), Eu (3.87) and Y (Y/Ho 68.66), and LREE/HREE and MREE/HREE relationships of0.89 and 1.14, respectively. These characteristics indicate that GB chert corresponds to C-Chert sensu-stricto, while GVA chert is comparable with SChert dueto Y/Ho ratios - 31, and Eu anomalous contents between 1.2 and 1.4. This new geochemical evidence allows confirming the presence of cherts in the El Cortijo Formation that have been formed in an ocean basin before to the collision of Tandilia with the Rio de la Plata Craton.